BIDRAG TILL EN FIKTIONOLOGISK EPISTEMOLOGI - Rossholm, Göran (K&K - Kultur og Klasse, 2013)
A CONTRIBUTION TO NARRATIVE EPISTEMOLOGY | In the wake of Roman Ingarden’s Das Literarische Kunstwerk many literary theorists have claimed that fictional worlds are “incomplete”, contrary to our real world. This idea is critically examined; the conclusion of the examination is that in most cases the incompleteness thesis is based on confusion between ontology and epistemology. However, in some cases – one example is Kafka’s The Process – the thesis is better warranted, but in these cases incompleteness may just as well be described in semantic terms as vagueness.